Respostas
respondido por:
1
Boa noite!
vamos resolver..
3.(x + 2) - 5.(x + 3) = 1
aplica a distributiva..
3x + 6 - 5x - 15 = 1
- 2x - 9 = 1
- 9 - 1 = 2x
2x = - 10
x = - 10 / 2
x = - 5
Portanto, - 5 é raiz da equação
Bons estudos!
vamos resolver..
3.(x + 2) - 5.(x + 3) = 1
aplica a distributiva..
3x + 6 - 5x - 15 = 1
- 2x - 9 = 1
- 9 - 1 = 2x
2x = - 10
x = - 10 / 2
x = - 5
Portanto, - 5 é raiz da equação
Bons estudos!
respondido por:
2
Boa noite!!
3(x +2) -5(x+3) = 1
3x +6 -5x -15 = 1
-2x = 1 + 9
-2x = 10
x = 10/-2
x = -5
Sim, -5 é raiz da equação.
Bons estudos!
3(x +2) -5(x+3) = 1
3x +6 -5x -15 = 1
-2x = 1 + 9
-2x = 10
x = 10/-2
x = -5
Sim, -5 é raiz da equação.
Bons estudos!
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás